2020
DOI: 10.13004/kjnt.2020.16.e33
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Perforation Caused by Bone Cements as a Complication of Cement Augmented Pedicle Screw Fixation Using the Fenestrated Pedicle Screw: A Case Report

Abstract: Cement-augmented fenestrated pedicle screw fixation is becoming more popular for osteoporotic patients. Although several reports have been published on leakage-related problems with bone cement, no cases of cardiac perforation after cement-augmented pedicle screw fixation have been reported. We present a case of cardiac perforation after cement-augmented fenestrated pedicle screw fixation. A 67-year-old female was admitted to our hospital with complaints of dyspnea and chest pain after lumbar surgery. She had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…They identified 68 cases with cement leakage into paravertebral veins or the ascending vena cava and 13 patients with pulmonary cement embolism (7.9%), of whom five (3.0%) were symptomatic. In addition, a case of cardiac perforation caused by bone cement, closely resembling our situation, was reported as a complication of CAPS, 6 wherein the authors reported the presence of a sharp and large fragment (4.5-cm-sized and needle-shaped). In their case, the authors detected cement leakage 7 days after spine surgery and performed anterolateral thoracotomy under one-lung ventilation for its removal.…”
Section: Percutaneous Endovascular Retrieval Of Large Cement Leakage Into the Right Atrium Following Cement-augmented Pedicle Screw Instrsupporting
confidence: 65%
“…They identified 68 cases with cement leakage into paravertebral veins or the ascending vena cava and 13 patients with pulmonary cement embolism (7.9%), of whom five (3.0%) were symptomatic. In addition, a case of cardiac perforation caused by bone cement, closely resembling our situation, was reported as a complication of CAPS, 6 wherein the authors reported the presence of a sharp and large fragment (4.5-cm-sized and needle-shaped). In their case, the authors detected cement leakage 7 days after spine surgery and performed anterolateral thoracotomy under one-lung ventilation for its removal.…”
Section: Percutaneous Endovascular Retrieval Of Large Cement Leakage Into the Right Atrium Following Cement-augmented Pedicle Screw Instrsupporting
confidence: 65%
“…Most cardiac perforations occurred in the right atrium 4 and ventricle. 5 However, in our case, perforations were found in both the right atrial wall and the aorta facing the right atrial wall. The leading cause of cardiac tamponade and hypotension in this case was aortic bleeding.…”
Section: Discussioncontrasting
confidence: 48%
“…Two major types of CAPS were found depending on the screw type: Conventional solid screws: cement-brushed solid screw inserted [ 19 ] or solid screw inserted after vertebroplasty [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 20 , 21 , 22 , 23 ]. Fenestrated screws ( Figure 1 ): these can be cemented after screw placement [ 11 , 12 , 13 , 14 , 15 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. …”
Section: Methodsmentioning
confidence: 99%
“…However, while CAPS is being increasingly used, post-CAPS cement leakage is a considerable problem. Cement leakage into the spinal canal can cause spinal cord compression symptoms, including neurologic deficits and pain, while leakage into the epidural vein, vena cava, right atrium, pulmonary artery, or multiple lung arterioles can cause cardiac or pulmonary cement embolism (PCE) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Since both embolisms have the same pathology, this study included cardiopulmonary cement embolisms after CAPS as CPCE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation